Konsistensi Pertimbangan Hakim Upaya Mewujudkan Kepastian Hukum dalam Sengketa Perdata Kepemilikan Tanah: Analisis Putusan Nomor 16/PDT/2020/PT PLG - Immoto Qoonita Naflah Maulana; Siti Dhiya Tiara; Keysyah Aulia Hidayat; Sri Handayani (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
This research aims to analyze the consistency of judges' legal reasoning in deciding land ownership disputes and its implications for the fulfillment of the principle of legal certainty. The primary focus of this study is directed at Decision Number 16/PDT/2020/PT PLG, where differences in legal perception or evidentiary evaluation occurred at the appellate level. Land disputes are a crucial issue that requires legal firmness to avoid uncertainty for justice seekers. The research method used is normative legal research with a case approach and a statutory approach. Data were sourced from secondary data consisting of primary, secondary, and tertiary legal materials, analyzed qualitatively. The results show that the consistency of the judges' reasoning in Decision Number 16/PDT/2020/PT PLG depends heavily on the accuracy of assessing evidence, particularly documentary evidence (certificates) and witness testimony. Inconsistency between factual considerations and the application of legal norms has the potential to undermine the principle of legal certainty. This study concludes that strengthening the standards of legal reasoning based on the principle of ex aequo et bono and adherence to civil procedural law is absolutely necessary so that judicial decisions do not only resolve disputes procedurally but also provide certainty of ownership rights for thelitigating parties.